Measuring brain activity associated with subsequent relational memory in typically developing periadolescent children: preliminary data from the PRANK study. (20th December 2022) - Ramirez, Meghan K; Sexton, Jennifer N; Phipps, Connor J; Behm, Lillian; DeCesare, Thomas A; Heller, Abi M; Maerlender, Arthur C.; Phatak, Vaishali S; Cramer, Justin A.; Blair, James; Murman, Daniel L; Warren, David E
Abstract: Background: The developing brain undergoes significant structural and functional changes that are associated with substantial cognitive changes, and this maturational trajectory continues during the periadolescent epoch. One such change is improvement in relational memory (RM) abilities. Normal RM requires the hippocampus, as demonstrated by the distinct memory deficits of Alzheimer's disease (AD) associated with AD‐related hippocampal pathology. Lifelong risk factors for late onset AD may affect childhood brain development in ways that affect vulnerability to AD and other memory deficits later in life. This possibility motivates investigation into the brain's developmental trajectory and correlations with AD‐vulnerable cognitive abilities, especially memory. Method: Our ongoing NIA‐funded study, the Polygenic Risk of Alzheimer's Disease in Nebraska Kids (PRANK) study, measures brain structure, function, and cognitive abilities in periadolescent children (age 8–13 years). Here, we report preliminary data using task‐based fMRI and a subsequent memory (SM) paradigm to measure hippocampal‐dependent RM. A periadolescent sample from the PRANK study provided data for the current project (N = 90). MRI data were collected using protocols adapted from the Human Connectome Project. Hippocampal‐dependent RM was tested using a subsequent memory task where participants were asked to study pairs of common objects while fMRI‐BOLD data were collected. A memory test was completed for the studied materials where participants were presented two types of stimuli (studied match pairs or mismatched pairs of studied items). Result: Successful SM was associated with increased activity consistent with the frontoparietal networks in the lateral prefrontal and lateral parietal regions, increased activity in the dorsal attention network, and decreased activity in the so‐called memory retrieval network. There was evidence of increased anterior hippocampal activity associated with successful SM. Conclusion: Using task‐based fMRI to study brains of periadolescent children while they studied pairs of items, we observed SM effects that implicated anterior hippocampus and large‐scale functional brain networks (frontoparietal, dorsal attention, and memory retrieval). Findings from this preliminary analysis are novel in this task and in this population but concordant with previous studies of older and younger individuals. Future work will test whether there is an association in the magnitude of SM effects with polygenic risk for AD among PRANK participants.